Derailing the aspartate pathway of Mycobacterium tuberculosis to eradicate persistent infection - Erik J. Hasenoehrl (Nature Portfolio, 2019)
Amino acid biosynthetic pathways are an attractive alternative to treat chronic infections such as Mycobacterium tuberculosis (Mtb). Here, the authors investigate the metabolic response to disruption of the aspartate pathway in persistent Mtb and identify essential enzymes as potential new targets for drug development.